Eye Movement Desensitization and Reprocessing vs. Treatment-as-Usual for Non-Specific Chronic Back Pain Patients with Psychological Trauma: A Randomized Controlled Pilot Study - Gerhardt, Andreas; Leisner, Sabine; Hartmann, Mechthild; Janke, Susanne; Seidler, Günter H.; Eich, Wolfgang; Tesarz, Jonas (Frontiers in Psychiatry, 2016)
Objective: Eye-Movement-Desensitization and Reprocessing (EMDR) – an evidence-based approach to eliminate emotional distress from traumatic experiences – was recently suggested for the treatment of chronic pain. Aim of this study was to estimate preliminary efficacy of a pain-focused EMDR intervention for the treatment of non-specific chronic back pain. Design: Randomized controlled pilot study. Methods: Forty non-specific chronic back pain patients reporting previous experiences of psychological trauma were consecutively recruited from outpatient tertiary-care pain centers. After baseline assessment, patients were randomized to intervention or control group (1:1). The intervention group received ten sessions standardized pain-focused EMDR in addition to treatment-as-usual. The control group received treatment-as-usual alone. The primary outcome was preliminary efficacy, measured by pain intensity, disability, and treatment satisfaction from the patients' perspective. Clinical relevance of changes was determined according to established recommendations. Assessments were conducted at the baseline, post-treatment, and at a 6-month follow-up. Intention-to-treat-analysis with last-observation-carried-forward method was used. Registered with ClinicalTrials.gov (NCT01850875). Results: Estimated effect sizes (between-group, pooled standard deviation) for pain intensity and disability were d=0.79 (CI95%: 0.13, 1.42) and d=0.39 (CI95%: -0.24, 1.01) post-treatment, and d=0.50 (CI95%: 0.14, 1.12) and d=0.14 (CI95%: -0.48, 0.76) at 6-month follow-up. Evaluation on individual patient basis showed that about 50% of the patients in the intervention group improved clinically relevant and also rated their situation as clinically satisfactory improved, compared to zero patients in the control group. Conclusions: There is preliminary evidence that pain-focused EMDR might be useful for non-specific chronic back pain patients with previous experiences of psychological trauma, with benefits for pain intensity maintained over six months.